Macroeconomic, international trade and sectoral policies in livestock development. An analysis with particular reference to low income countries - Williams, Timothy O.; Rosa, D.A. de; Badiane, O. (Food and Agriculture Organization of the United Nations, 1995)
Following a general introduction Section 1 review regional trends in production, consumption and trade and highlights some related policy issues. Section 2 then considers in conceptual terms the importance of macroeconomic, trade and other economic policies to provide a basis for the remainder of the paper. Section 3 examines agricultural and livestock development in major developing regions in relation to macroeconomic and trade policies whereas Section 4 looks at livestock sector policies. Recent West African experiences in livestock production and trade against a background of changes in international and regional economic policies are the focus of Section 5. The concluding Section 6 focuses on appropriate economic policies for livestock development in low income countries.